Prevalence of Health and Nutrient Content Marketing Strategies on Breakfast Cereal Packages Before and After a Countrywide Marketing and Labeling Regulation: A Focus on Chile - Stoltze, Fernanda Mediano (Curr Dev Nutr, 2020)
OBJECTIVES: Chile's Food Labeling Law requires packaged foods that exceed certain thresholds for sugars, saturated fats, sodium, and calories to use one or more front of package warning logos identifying the excessive nutrient, and restricts the use of nutrient claims (e.g., lower sugar) contradicting its warning (e.g., high in sugar). We examined health- and nutrition-related marketing on breakfast cereals packages that did vs. did not qualify for a “high in” logo in packages photographed before and after the law implementation. METHODS: Photographs were taken in 6 supermarkets in Santiago before (n = 168) and after (n = 146) implementation. Breakfast cereals were classified by whether or not they had high levels of sugar, sodium, saturated fat, or calories according to the regulation, and thus were required to carry a warning label. Packages were analyzed for the presence of low-in and high-in nutrient claims and the following health appeals: health benefits, general healthiness, healthy habit recommendations, and medical endorsements. RESULTS: About 79% of products at pre-implementation and 59% of products at post-implementation qualified as “high in.” Of the post-implementation “high in” products, 93% displayed at least one warning logo. Comparing pre-implementation vs. post-implementation, the percentage of “high in” products that used at least one nutrient claim (92% vs. 86%) or health appeal (81% vs. 77%) did not change significantly. However, low-in claims (51% vs. 29%) and health benefit claims (10% vs. 1%), specifically, decreased after implementation, P < .05. Among “non high in” packages, the percentage of products that used health appeals (75% vs. 95%) increased post-implementation, P < .05. Medical endorsements, specifically, were less prevalent at post-implementation among both “high in” (from 23% to 0%) and “non high in” products (from 25% to 5%), P < .05. CONCLUSIONS: After implementation of the Chilean law, 93% of “high in” breakfast cereal packages complied with the use of warning logos. Featuring these warnings appears to have reduced the prevalence of “low in” claims among “high in” cereals. However, the law did not appear to affect the prevalence of other health- and nutrient-related marketing strategies. FUNDING SOURCES: Bloomberg Philanthropies, International Development Research Center, and Chilean National Agency of Research and Development.